Robot-Assisted Thoracoscopic Tumor Resection of Lymph Node Metastasis of an Unknown Primary Site: A Case Report - Tamami Isaka; Shota Mitsuboshi; Hiroaki Shidei; Hiroe Aoshima; Takako Matsumoto; Tatsuo Sawada; Yoji Nagashima; Masato Kanzaki (Tokyo Women's Medical University Journal, 2020)
Cancer of an unknown primary site (CUP) accounts for approximately 3% of all cancer cases. Among these cases, mediastinal lymph node cancer is comparatively rare, and there are no established treatment methods or approaches. Excision of CUP is feasible with the best methods. We herein report a case of mediastinal lymph node CUP resection by robot-assisted thoracoscopic surgery (RATS). The patient was a 60-year-old man. A chest computed tomography (CT) scan identified swelling in the mediastinal lymph node (right tracheobronchial lymph node; #4R) with another organ suspected as the site of the primary lesion, but it was not detected through positron emission tomography (PET). The patient was diagnosed with CUP with lymph node metastasis and mediastinal lymph node dissection was performed via RATS. Histopathological examination revealed desmoplasia in the lymph nodes. Immunohistochemically, the tumor was positive for CK7, TTF1, and napsin A, but negative for CK20, CK5/6, CDX2, p40, and AFP, indicating lung-derived adenocarcinoma. In the narrow space such as the mediastinum, RATS is a useful procedure for resectable mediastinal tumors.